Controle de Cosmopolites sordidus [(Germar, 1824) (Coleoptera: Curculionidae)] com Beauveria caledonica em solução oleosa - Tavares, Nathália Gama (Universidade Federal de São Carlos, 2023)
Banana is one of the most consumed and produced fruits worldwide, in Brazil it has wide gastronomic acceptance, so that only 1% of Brazilian production is exported, therefore, it is a fruit of great internal importance. The main pest of the crop is the banana borer known as Cosmopolites sordidus [(Germar, 1824) (Coleoptera: Curculionidae)]. In the adult stage, this insect is dark, almost black, and in the young stage the larvae build galleries in the rhizome, causing damage to the plants. The present work aimed to evaluate different concentrations of Beauveria caledonica in oily solution.This entomopathogenic fungus is little studied worldwide for the control of the insect pest. B. caledonica spores and blastospores were evaluated in emulsifiable oil, to increase the pest's mortality potential, through spraying on the insect's back, which were kept in individual trays with food for 23 days in BOD and evaluated daily. Dead insects were collected and relocated on Elisa plates to confirm death by contamination. The results obtained were subjected to analysis of variance and Tukey's test at a 5% level using the R software, and graphs to visualize the mortality rate were made using the Excel program. Treatment 8 was the one that presented the best result, totaling 37 dead out of 60 insects tested from the 10th day after spraying, however, it did not differ statistically from treatment 10, therefore, it was possible to state that the two treatments were the best among those tested and can be recommended for future research involving the entomopathogenic fungus. It was concluded that treatments 8 and 10, with a concentration of 1x108 conidia/mL and 5x107 blastospores/mL, caused the highest insect mortality rate. Blastospores from Beauveria caledonica also functioned as controls for Cosmopolites sordidus. And the use of emulsifiable oil increased the insecticidal activity.
Control of Cosmopolites sordidus [(Germar, 1824) (Coleoptera: Curculionidae)] with Beauveria caledonica in oil suspension
Keywords: Controle biológico; Broca-da-bananeira; Fungo entomopatogênico; Manejo Integrado de Pragas.; Biological control; Banana weevil borers; Entomopathogenic fungus; Integrated Pest Management; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE